Electrochemical determination of ascorbic acid and paracetamol in pharmaceutical formulations using a glassy carbon electrode modified with multi-wall carbon nanotubes dispersed in polyhistidine - Dalmasso, Pablo Roberto (2012)
This work reports on the analytical performance of glassy carbon electrodes (GCE) modified with a dispersion of multi-wall carbon nanotubes (MWCNT) in polyhistidine (Polyhis) (GCE/MWCNT-Polyhis) for the simultaneous determination of ascorbic acid (AA) and paracetamol (PA). The modified electrode exhibited enhanced current responses and lower oxidation overvoltages, demonstrating excellent catalytic activities towards AA and PA oxidation compared to bare GCE. The linear dependence between the anodic peak currents and the square root of scan rates over the range of 0.005-0.300 V/s demonstrate that the electrooxidation of AA and PA occurs under diffusional control. The MWCNT-Polyhis modified GCE displayed a sensitivity of (3.8 ± 0.1) ×104 µA/M (r = 0.998) and a detection limit of 0.76 µM for the selective determination of AA in the presence of 1.00 × 10-4M PA. Conversely, for the direct quantification of PA in the presence of 5.00 ×10-4M AA, the sensitivity and the detection limit were (6.3 ± 0.2) ×105µA/M (r = 0.997) and 32 nM, respectively. The proposed electrochemical sensor was successfully applied for quantifying AA and PA in commercial pharmaceutical formulations without any sample pretreatment.